Bacterial Community of Heermann’s Gull (Larus heermanni): Insights into Their Most Common Species and Their Functional Role during the Breeding Season in the Gulf of California - Enrico A. Ruiz; Araceli Contreras-Rodríguez; Oliva Araiza; Ma G. Aguilera-Arreola; Juan A. Hernández-García; José J. Flores-Martínez; Víctor Sánchez-Cordero; Zulema Gomez-Lunar (Diversity)
The seabird intestinal microbiota, or bacteriome, predominantly consists of bacteria that establish during embryonic development through vertical transfer from females and horizontal transfer during growth and copulation. This study focuses on the Heermann’s Gull (Larus heermanni), a seabird that breeds mainly within the Gulf of California. Our goal was to understand its gut bacteriome composition and its implications for conservation and public health. Using microbiological techniques, 16S rRNA gene sequencing, and mass spectrometry, we characterized the HG gut bacteriome and compared it with other bird species. Our findings reveal a diverse bacteriome, particularly in the intestine and rectum, with dominant phyla including Firmicutes, Proteobacteria, Bacteroidetes, Cyanobacteria, and Fusobacteria. Seasonal and sex-related differences were observed, with significant correlations between some pairs of bacteria. Notably, we identified various pathogens and potential zoonotic bacteria, underscoring the public health risks associated with Heermann’s Gull interaction with humans and other animals. These results highlight the importance of the Heermann’s Gull gut bacteriome in nutrient production, pathogen control, and digestive health, and emphasize the need for further research on pathogen transmission involving seabirds. Our study provides crucial insights for conservation strategies and underscores the role of wild birds in the epidemiology of zoonotic diseases.